Odpowiedzi

Najlepsza Odpowiedź!
  • ucz
  • Początkujący
2010-02-10T19:35:22+01:00
A) 3x-4=4x
3x-4x=4 ---> 3*(-4)-4*(-4)=4
-x=4 *(-1) -12+16=4
x=-4 4=4
L=P

b)-27x+1=2x+59
-27x-2x=59-1 -----> -27*(-2)-2*(-2)=58
-29x=58 /:(-29) 54+4=58
x=-2 58=58
L=P


c)82x-9=-18x+1
82x+18x=1+9 ----> 82*0,1+18*0,1=10
100X=10 /:100 8,2+1,8=10
x=0,1 10=10
L=P
1 5 1
2010-02-10T19:43:26+01:00
A)
3x-4=4x [-4x
-x-4=0 [+4
-x=4 [*(-1)
x=-4

b)
-27x+1=2x+59 [-2x
-29x+1=59 [-1
-29x=58 [/(-29)
x=-2

c)
82x-9=-18x+1 [+18x
100x-9=1 [+9
100x=10 [/100
x=0,1

1 5 1